2022
DOI: 10.1021/acsagscitech.1c00253
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas System: Applications and Prospects for Maize Improvement

Abstract: Maize (Zea mays) is one of the most important cereal crops to secure food supplies in the world. A growing world population requires new approaches to facilitate and accelerate maize breeding. As a powerful tool, the CRISPR/Cas system has revolutionized the fields of functional genomics and crop breeding. Compared to cross breeding and transgenic breeding, genome-editing breeding based on CRISPR/Cas will bring new opportunities in rapidly cultivating novel maize varieties with desired characteristics. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…Such redundancy is difficult to detect by traditional mutagenesis and map-based cloning, but CRISPR/Cas9-mediated gene mutagenesis provided a new opportunity. It is worth noting that 15 of the 34 maize GMS genes were validated via CRISPR/Cas9 technology within the last two years [ 68 , 150 , 151 , 216 ]. We thus constructed and updated the working model regulating maize anther and pollen development ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such redundancy is difficult to detect by traditional mutagenesis and map-based cloning, but CRISPR/Cas9-mediated gene mutagenesis provided a new opportunity. It is worth noting that 15 of the 34 maize GMS genes were validated via CRISPR/Cas9 technology within the last two years [ 68 , 150 , 151 , 216 ]. We thus constructed and updated the working model regulating maize anther and pollen development ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…We thus constructed and updated the working model regulating maize anther and pollen development ( Figure 5 ). A large number of studies have demonstrated that the GMS genes tend to be specifically expressed in the anther [ 49 , 211 , 216 ]; thus, we should focus on the rapid isolation of anther-specific genes and then validate their functions by CRISPR/Cas9 mutagenesis, which is crucial for thoroughly unraveling the molecular regulatory network underlying maize anther and pollen development. Recently, different kinds of BMS systems in maize, including SPT, MCS and DGMS, have been established [ 42 , 43 , 44 , 169 , 170 , 174 , 178 , 179 ]; the newly identified GMS genes can be tested for their potential in increasing maize yield via the utility of BMS systems.…”
Section: Discussionmentioning
confidence: 99%
“…Gene-editing technologies can efficiently introduce precise and predictable gene mutations into plants to obtain desired phenotypes [13,14]; the CRISPR/Cas system is the most popular system due to its specificity, simplicity, flexibility, and versatility [15]. Multiplex gene editing can be achieved with Cas9 nuclease through expressing Cas9 along with multiple gRNAs [16], which has been successfully used to dissect the functions of gene family members with redundant functions in plants [17].…”
Section: Introductionmentioning
confidence: 99%
“…When the engineered T cells have become mature, researchers introduced the CRISPR/Cas9 technology into the therapy of recurrent and refractory hematologic malignancies [ 6 ]. In addition, the CRISPR/Cas9 technology has also been widely used in crop breeding [ 7 ], including the development of fine-tuning gene regulation, traits improvement, virus resistance enhancement, etc. [ 8 ].…”
Section: Introductionmentioning
confidence: 99%